2022
DOI: 10.1021/acsami.1c24748
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulation of Telmisartan-Loaded PCL/PVP Scaffolds on Macrophages Promotes Endogenous Bone Regeneration

Abstract: Biomaterial–immune system interactions play an important role in postimplantation osseointegration to retain the functionality of healthy and intact bones. Therefore, appropriate osteoimmunomodulation of implants has been considered and validated as an efficient strategy to alleviate inflammation and enhance new bone formation. Here, we fabricated a nanostructured PCL/PVP (polycaprolactone/polyvinylpyrrolidone) electrospinning scaffold for cell adhesion, tissue ingrowth, and bone defect padding. In addition, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 89 publications
1
18
0
Order By: Relevance
“…Particular focus has been placed on the role of phenotype switching, which remains controversial [ 253 ]. For instance, a recent study has revealed the utilization of a nanostructured polycaprolactone (PCL)/polyvinylpyrrolidone electrospun biomaterial in bone tissue regeneration via polarization of macrophages toward the M2 phenotype [ 254 ]. Generally, immunomodulation through biomaterials can be achieved via various strategies, including: 1) mediation of their physicochemical properties, 2) delivery of immunoregulatory activators, and 3) alteration of their mechanical properties [ 255 ].…”
Section: Biomaterials Involved In the Regulation Of The Immune Microe...mentioning
confidence: 99%
“…Particular focus has been placed on the role of phenotype switching, which remains controversial [ 253 ]. For instance, a recent study has revealed the utilization of a nanostructured polycaprolactone (PCL)/polyvinylpyrrolidone electrospun biomaterial in bone tissue regeneration via polarization of macrophages toward the M2 phenotype [ 254 ]. Generally, immunomodulation through biomaterials can be achieved via various strategies, including: 1) mediation of their physicochemical properties, 2) delivery of immunoregulatory activators, and 3) alteration of their mechanical properties [ 255 ].…”
Section: Biomaterials Involved In the Regulation Of The Immune Microe...mentioning
confidence: 99%
“…Based on experimental results, using fibers loaded with telmisartan enhances this interaction, exhibiting pro-osteogenic properties on bone marrowderived mesenchymal stem cells (BMSCs). 121 Additionally, Ye et al designed a core-shell-structured suture for acute tendon rupture surgery. In their construction, the polyamide (PA)-6 (PA-6) with excellent mechanical strength was designed as the core, and while heparinloaded PLLA as the shell, the bilayer fiber structure was twisted into a rope for in vivo tissue suturing 122 ; compared with non-heparin-loaded suture group and commercial suture group, the high heparin concentration leads to milder inflammation and faster healing when applicated in vivo, indicating promising tissue repairing capability of this electrospun suture (Figure 7B).…”
Section: Immunoregulative Drug Loadingmentioning
confidence: 99%
“…Reproduced with permission. 121 Copyright 2022, American Chemical Society. (B) illustration the structure of electrospun sutures laden with heparin.…”
Section: Conflict Of Interest Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…Biomaterials can be created and produced into scaffolds for skull deformities using the generated digital data [ 13 , 15 ]. Calcium phosphate bone cements [ 16 ], polymers [ 17 , 18 ], titanium alloy [ 19 ], CuS-PEG-PCL scaffold [ 20 ] and other materials are currently widely used in skull and bone deformities [ 21 , 22 , 23 , 24 ]. The defect position can be covered and protected by the skull defect repair scaffold.…”
Section: Introductionmentioning
confidence: 99%